Erratum to: Singlet night in Feynman-ville: one-loop matching of a real scalar - Ulrich Haisch; Maximilian Ruhdorfer; Ennio Salvioni; Elena Venturini; Andreas Weiler (Journal of High Energy Physics, 2020)
Due to an oversight, in the original paper we did not give the one-loop matching correction to the (non-hermitian) operator.